Síntesis de óxidos mixtos de mn-fe mediante el método de autocombustión para la degradación de cristal violeta en aguas residuales (2018)
The present undergraduate thesis contributes to the synthesis, characterization, selection and order of reaction of catalysts prepared by the self-combustion method using transition metals of Mn and / or Fe, thus evaluating a possible cooperative effect between these metals and their interaction in terms of its physicochemical properties of the material and its catalytic behavior in the degradation of crystal violet (CV) in aqueous medium diluted to moderate conditions